Custodial and perinatal care patterns of women who received prenatal care while incarcerated in the Arkansas state prison system, 2014-2019 - Melissa J. Zielinski; Mollee Steely Smith; Alleigh Stahman (BMC, 2024)
Abstract Background The extraordinary growth in women's incarceration over the past several decades has resulted in calls for expansion of research into their unique needs and experiences, including those related to pregnancy and perinatal care. However, while research into the health outcomes of women who are incarcerated while pregnant has grown, research on women's custodial and perinatal care patterns has remained nearly non-existent. Here, we sought to describe (1) the characteristics of the population of women who came to be incarcerated in a state prison system during pregnancy and (2) the characteristics of women's custodial and perinatal care patterns during and after incarceration. Methods We conducted a retrospective chart review of the population of women who received perinatal care while incarcerated in the Arkansas state prison system over a 5-year period from June 2014 to May 2019. Electronic medical records and state prison records were merged to form our study population. Data were from 212 women (Mage = 28.4 years; 75.0% non-Latina White) with a singleton pregnancy who received at least one obstetric care visit while incarcerated. Results Drug-related convictions were the most common crimes leading to women's incarceration while pregnant, and violent crime convictions were rare. Nearly half (43.4%) of women who gave birth in custody did so within 90 days of admission and the great majority (80.4%) released within 1-year of giving birth, including 13.3% who released within 30 days. Discussion The frequency with which women who became incarcerated while pregnant released from prison either prior to or shortly after giving birth was a striking, novel finding of this study given the implications for perinatal care disruption among a high-risk population and the harms of forced separation from infants within hours of birth. Conclusions Diversionary programs for pregnant women convicted of crimes, particularly in states without current access, are urgently needed and should be a priority for future policy work.